Hubungan PHBS dengan Kejadian ISPA Di Desa Tarai Bangun Wilayah Kerja Puskesmas Tambang - Nurlinda, Nurlinda; Apriyanti, Fitri; Alini, Alini (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Acute respiratory infections (ARI) are still a world health problem, acute respiratory tract diseases are easily transmitted to toddlers who in their environment do not meet the criteria for clean and healthy living and this is a problem that is often encountered in the surrounding community. The purpose of the study was to determine the relationship between clean and healthy living behavior (PHBS) with the incidence of acute respiratory infections (ARI) in toddlers in Tarai Bangun Village, Tambang Health Center Work Area. This type of research is quantitative with a cross sectional design. The population of this study were all parents of children under five who visited the posyandu in July 2022 with a total sample of 117 and taken using the total sampling technique. The data collection tool uses a questionnaire. Analysis of the data used is univariate and bivariate analysis with chi-square test. Based on univariate analysis were obtained from 117 parents of children under five, there were 67 parents of children under five (57.3%) who were not good at implementing PHBS and as many as 69 children under five (59.0%) experience ARI.The results of statistical tests showed that there was a relationship between clean and healthy living behavior (PHBS) and the incidence of acute respiratory infections (ARI) in children under five in Tarai Bangun Village, Mining Health Center Working Area (P-value = 0.000). It is hoped that parnts of toddlers in Tarai Bangun Village, Tambang health center work area can implement clean and healthy living behavior (PHBS) by getting used to living clean and healthy.